THE CHALLENGES OF LEADERSHIP IN A MULTINATIONAL COMPANY IN THE MOTORCYCLE PARTS SECTOR - Pereira da Silva, David Murilo; Freire, José Eduardo (Revista Interface Tecnológica, 2020)
The corporate environment is increasingly competitive, and it is necessary to invest in human talent, especially in leaders who are able to motivate their employees and make them feel committed to the organization’s objectives. In previous decades it focused mainly on the products and services delivered, currently the focus of interest becomes for people. In this scenario arises the importance of the actions of leaders, mainly in the development of techniques and application of knowledge, skills and attitudes in management processes. The main objective of this work was to identify the type of leadership used by the organization under study and whether it has been effective. In order to achieve this objective, bibliographical research on the subject was first made and a field research applied to the section leaders of the company under study, using the interview as a data collection tool. After this research it was concluded that most leaders seek the democratic style, which is in line with the leadership style that the company supports and believes in better results.